The nonverbal advantage secrets and science of body language at work - Goman, Carol Kinsey (San Francisco Berrett-Koehler Publishers, 2008)
The workplace is a ?blink? world: studies show that we form opinions of one another within seven seconds of meeting and that 93 percent of the messages people receive from us have nothing to do with what we actually say. So the ability to recognize and develop good nonverbal communication skills can be a huge professional advantage.
Includes index.
Keywords: Body language